Epidemiology of acute poisoning in children presenting to the poisoning treatment center at Ain Shams University in Cairo, Egypt, 2009–2013. (2nd January 2016) - Azab, Sonya M. S.; Hirshon, John Mark; Hayes, Bryan D.; El-Setouhy, Maged; Smith, Gordon S.; Sakr, Mahmoud Lotfy; Tawfik, Hany; Klein-Schwartz, Wendy
Abstract: Introduction : Pediatric poisonings represent a major and preventable cause of morbidity and mortality throughout the world. Epidemiologic information about poisoning among children in many lower- and middle-income countries is scarce. This study describes the epidemiology of acute poisonings in children presenting to Ain Shams University's Poisoning Treatment Center (ASU-PTC) in Cairo and determines the causative agents and characteristics of acute poisoning in several pediatric age groups. Methods : This retrospective study involved acutely poisoned patients, 0–18 years of age, who presented to the ASU-PTC between 1 January 2009 and 31 December 2013. Data were extracted from electronic records maintained by the ASU-PTC. Collected data included demographics, substance of exposure, circumstances of the poisoning, patient disposition, and outcome. Results : During the 5-year study period, 38 470 patients meeting our criteria were treated by the ASU-PTC; 19 987 (52%) were younger than 6 years of age; 4196 (11%) were 6–12 years; and 14 287 (37%) were >12 years. Unintentional poisoning accounted for 68.5% of the ingestions, though among adolescents 84.1% of ingestions were with self-harm intent. In all age groups, the most frequent causative drugs were non-opioid analgesics, antipyretics, and antirheumatics. The most common nonpharmaceutical agents were corrosives in preschool children and pesticides in adolescents. Most patients had no/minor effects (29 174 [75.8%]); hospitalization rates were highest among adolescents. There were 119 deaths (case fatality rate of 0.3), primarily from pesticide ingestion. Conclusion : Poisoning in preschool children is mainly unintentional and commonly due to nonpharmaceutical agents whereas poisoning in adolescents is mainly intentional (self-harm). Pesticides, mainly organophosphorous compounds and carbamates, were the most frequent agents leading to morbidity and mortality.